BUDAYA RIMPU DI KALANGAN ANAK MUDA BIMA - Suci yati; Endang Nila Hardianti; Khusnul Khatimah; Mr Bustan (Rayhan Intermedia, 2019)
This research was done to find out how to community understood, especially among Bima young people in the Simpasai village of Lambu subsdistrict regarding rimpu, which became the culture of dou mbojo. This type of research is qualititave research using the library research method and field research. Data is obtained by observing first, and conducting interviews and literature review by interviewing informations, such as community leaders, village staff, weavers, academies and the general public in Simpasai village and Lambu sub-district. The result of the study show that rimpu has meaningand value that make it a characteristic for dou mbojo, both in terms of use and meaning. In addition, the use of rimpu is inseparable from the use of typical Bima tembe. Tembe has different patterns and motifs. Weavers who make it the pattern according to their needs. Although now the rimpu starts to disappear from the life of dou mbojo, but it is just the form. The are still values that are trying to be preserved.